Investigating the molecular genetic, genomic, brain structural, and brain functional correlates of latent transdiagnostic dimensions of psychopathology across the lifespan: Protocol for a systematic review and meta-analysis of cross-sectional and longitudinal studies in the general population - Hoy, Nicholas; Lynch, Samantha; Waszczuk, Monika; Reppermund, Simone; Mewton, Louise (Frontiers in Psychiatry, 2022)
ABSTRACT Background: Research using latent variable modelling has identified a superordinate general dimension of psychopathology (i.e., the p-factor), as well as several specific/lower-order transdiagnostic dimensions (e.g., internalising, externalising) within the meta-structure of psychiatric symptoms. These models can facilitate discovery in genetic and neuroscientific research by providing empirically derived psychiatric phenotypes, offering greater validity and reliability than traditional diagnostic categories. The prospective review aims to integrate and assess evidence from research investigating the psychobiological correlates of general and specific/lower-order dimensions of psychopathology. Cross-sectional and longitudinal studies investigating general population samples of any age group or developmental period will be included to capture evidence from across the lifespan. Methods and analysis: MEDLINE, Embase, and PsycINFO databases will be systematically searched for relevant literature. The review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eligibility criteria were designed to capture psychiatric genetic (i.e., molecular genetic, genomic) and neuroimaging (i.e., brain structural, brain functional) studies investigating latent transdiagnostic dimension(s) or structural model(s) of psychopathology across any age group. Studies which include or exclude participants based on clinical symptoms, disorders, or relevant risk factors (e.g., history of abuse, neglect, trauma) will be excluded. Biometric genetic research (e.g., twin, family studies), candidate gene studies, neurophysiology studies and other non-imaging based neuroscientific studies (e.g., post-mortem studies) will be excluded. Study quality and risk of bias will be assessed using the Joanna Briggs Checklist for Analytical Cross-Sectional Studies, the Joanna Briggs Checklist for Cohort Studies, and the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) system. Meta-analysis will be conducted if sufficient data is available. Discussion: This protocol outlines the first systematic review to examine evidence from studies investigating the latent structure and underlying biology of psychopathology and to characterise these relationships developmentally across the lifespan. The prospective review will cover a broad range of statistical techniques and models used to investigate latent transdiagnostic dimensions of psychopathology, as well as a numerous genetic and neuroscientific methods. Systematic Review Registration: International Prospective Register for Systematic Reviews (PROSPERO; CRD42021262717).